Cardiac Pathology A Guide to Current Practice - Suvarna, Simon (Springer London : Imprint: Springer, 2013)
Cardiac disorders are an exciting area of classic pathology and recently defined disease. Cardiac Pathology: A Guide to Current Practice discusses the various disorders and also provides a backdrop of developmental embryology, diagnostic imaging and current therapeutics. Cardiac Pathology: A Guide to Current Practice aims to deliver in bench-book format a comprehensive overview of cardiac pathology that is relevant to those practicing in surgical pathology and autopsy arenas. Clear illustrations of the common styles of dissection are provided along with the normal anatomy and histology. Chapters cover the approach to the autopsy heart, ischemic heart disease, myocarditis, sudden death, valvular disease, transplant pathology, cardiomyopathy, cardiac neoplasia and congenital heart disease with a clear analysis of diagnostic criteria (macroscopic, microscopic and genetic) for both common cardiac diseases and those of rare format. The text is accompanied by high-quality macroscopic and microscopic images and references to other in-depth specialty data sources. Although aimed in particular at pathologists, Cardiac Pathology: A Guide to Current Practice should also be of value to cardiologists, cardiothoracic surgeons and other professions allied to medicine.